A Survey of Tick Surveillance and Control Practices in the United States. Issue 4 (17th June 2020) - Mader, Emily M; Ganser, Claudia; Geiger, Annie; Harrington, Laura C; Foley, Janet; Smith, Rebecca L; Mateus-Pinilla, Nohra; Teel, Pete D; Eisen, Rebecca J
Abstract: Tickborne diseases are an increasing public health threat in the United States. Prevention and diagnosis of tickborne diseases are improved by access to current and accurate information on where medically important ticks and their associated human and veterinary pathogens are present, their local abundance or prevalence, and when ticks are actively seeking hosts. The true extent of tick and tickborne pathogen expansion is poorly defined, in part because of a lack of nationally standardized tick surveillance. We surveyed 140 vector-borne disease professionals working in state, county, and local public health and vector control agencies to assess their 1) tick surveillance program objectives, 2) pathogen testing methods, 3) tick control practices, 4) data communication strategies, and 5) barriers to program development and operation. Fewer than half of respondents reported that their jurisdiction was engaged in routine, active tick surveillance, but nearly two-thirds reported engaging in passive tick surveillance. Detection of tick presence was the most commonly stated current surveillance objective (76.2%). Most of the programs currently supporting tick pathogen testing were in the Northeast (70.8%), Upper and Central Midwest (64.3%), and the West (71.4%) regions. The most common pathogens screened for were Rickettsia spp . (Rickettsiales: Rickettsiaceae) and bacterial and viral agents transmitted by Ixodes (Acari: Ixodidae) ticks. Only 12% of respondents indicated their jurisdiction directly conducts or otherwise financially supports tick control. Responses indicated that their ability to expand the capacity of tick surveillance and control programs was impeded by inconsistent funding, limited infrastructure, guidance on best practices, and institutional capacity to perform these functions.